Gunduk, Khanes, Gaugamela, Gali Zardak: notes on Navkur and nearby rock-cut sculptures in Kurdistan - Reade, Julian (Zeitschrift für Assyriologie und vorderasiatische Archäologie, 2013)
This paper discusses the rich but little-known Navkur plain, north-east of Nineveh, which is the probable location of the Battle of Gaugamela in 331 BC, and nearby rock-sculptures, with photographs illustrating new discoveries. The sculptures at Gunduk must now be dated to the mid-third millennium, and the evolution of the Khanes-Bavian sculptured complex can be followed from the Neo-Assyrian through the Greek, Parthian and Sasanian periods.